An analysis of actions to promote health in underprivileged urban areas: a case in Brazil - dos Reis Moreira, Érika Cardoso (BioMed Central, 2013)
BACKGROUND: Two policies stood out in the 2000s geared towards changing the care model adopted in Brazil: The National Policy on Primary Health Care, based on a family health care model, and the National Policy on Health Promotion. The aim of this study was to analyze health promotion actions developed by family health care teams in the municipality of Belford Roxo. This town was chosen by virtue of its “below average” level of primary health care services offered in relation to other municipalities in Rio de Janeiro state. METHODS: The following methodological strategies were employed: analysis of health systems, document analysis (2010 Annual Health Schedule and 2010 Annual Management Report), participant observation and interviews with nine health care professionals in the region of study, namely: the manager of the Regional Health Polyclinic (responsible for health care actions in the region), and nurses belonging to the eight family health teams. Giddens’ Theory of Structuration was used for analysis of the results. RESULTS: Varying levels of health care activity were found, indicating that the managers have been either unable or lacked the commitment to perform the proposed actions. From a structural point of view, 87.5% of the teams were incomplete. Also of particular note was the lack of any physicians in the teams, which, despite its detrimental effect, was regarded by the interviewees as “natural”. Strong political party influence in the area hindered relations between the team and the local population. Health education, especially through lectures was the main health promotion activity picked up in this study. No cross-sectorial or public participation actions were identified. Connections between the teams for sharing responsibilities were found to be very weak. CONCLUSION: In addition to political factors, there are also structural limitations such as a lack of human resources that overburdens the teams’ daily activities. From this point of view, the political context and lack of professionals were restrictive factors for health promotion. Belford Roxo is not necessarily representative of other experiences in Brazil. However, problems such as patronage, political manipulation, poverty and incipient cross-sectorial actions are common to other Brazilian towns and cities.